Potential Role for Combined Subtype-Selective Targeting of M1 and M3 Muscarinic Receptors in Gastrointestinal and Liver Diseases - Tolaymat, Mazen; Sundel, Margaret H.; Alizadeh, Madeline; Xie, Guofeng; Raufman, Jean-Pierre (Frontiers in Pharmacology, 2021)
Despite structural similarity, the five subtypes comprising the cholinergic muscarinic family of G protein-coupled receptors regulate remarkably diverse biological functions. This mini review focuses on the closely related and commonly co-expressed M1R and M3R muscarinic acetylcholine receptor subtypes encoded respectively by CHRM1 and CHRM3. Activated M1R and M3R signal via Gq and downstream initiate phospholipid turnover, changes in cell calcium levels, and activation of protein kinases that alter gene transcription and ultimately cell function. The unexpectedly divergent effects of M1R and M3R activation, despite similar receptor structure, distribution, and signaling, are puzzling. To explore this conundrum, we focus on the gastrointestinal (GI) tract and liver because abundant data identify opposing effects of M1R and M3R activation on the progression of gastric, pancreatic, and colon cancer, and liver injury and fibrosis. Whereas M3R activation promotes GI neoplasia, M1R activation appears protective. In contrast, in murine liver injury models, M3R activation promotes and M1R activation mitigates liver fibrosis. We analyze these findings critically, consider their therapeutic implications, and review the pharmacology and availability for research and therapeutics of M1R- and M3R-selective agonists and antagonists. We conclude by considering gaps in knowledge and other factors that hinder the application of these drugs and the development of new agents to treat GI and liver diseases.